Deciphering Developmental Epileptic Encephalopathies (DEE): Unravelling the Key Signs - Suryawijaya, Evlyne Erlyana; Lokito, Shania (Medicinus, 2024)
Background: Epilepsy, a chronic neurological disorder affecting over 50 million people worldwide, is marked by recurrent seizures and loss of consciousness. It is categorized based on EEG features, etiologies, and comorbidities. Developmental Encephalopathy (DE) involves developmental delays and early-onset seizures without causing developmental regression. In contrast, Epileptic Encephalopathy (EE) features severe epilepsy syndromes where frequent seizures result in developmental delays or regression.Methods: This review explores the clinical definitions, epidemiology, and diagnostic criteria for DE, EE, and DEEs. It covers their etiologies, clinical features, diagnostic methods, and treatment strategies, including genetic, structural, metabolic, and immune-related factors.Results: DE features developmental impairment with epilepsy, while EE involves severe epilepsy causing cognitive and behavioral dysfunction. DEEs are marked by early-onset severe epilepsy and EEG abnormalities that worsen developmental impairments. Essential diagnostic tools include EEG, neuroimaging, and genetic testing. Effective management requires personalized interventions to control seizures and address cognitive deficits.Conclusion: DEEs are a complex epilepsy subset with major developmental and cognitive challenges. Early diagnosis and targeted treatments are crucial for improving outcomes. Ongoing research into DEEs' genetic and pathophysiological mechanisms is key to enhancing understanding and management.